Comb‐Like Poly(Ether‐Sulfone) Membranes Derived from Planar 6, 12‐Diaryl‐5, 11‐Dihydroindolo[3, 2‐b]Carbazole Monomer for Alkaline Fuel Cells. Issue 21 (26th September 2016) - Zuo, Peipei; Su, Yumiao; Li, Wenmu
Abstract : Highly conductive anion exchange membranes (AEMs), along with the ability to suppress swelling, are critical but challenging requirements for alkaline fuel cell applications. To achieve this criterion, a series of poly(ether sulfone)s (PESFs) with flexible alkyl imidazolium pendants attached directly on large planar 6, 12‐bis(4‐hydroxyphenyl)‐5, 11‐dihydroindolo[3, 2‐b]carbazole (DCP) units is reported. The planar DCP units stabilize the hydrophobic phase through strong π‐π interactions and also facilitate the formation of ionic conducting channels through self assembly of hydrophilic pendants. The AEM prepared here, based on rational design, has a relatively low ion exchange capacity (IEC) of 1.86 × 10 –3 mol g –1 and exhibits high hydroxide ion (OH – ) conductivity of 101 × 10 –3 S cm –1, a low swelling ratio of 9.3% and a water uptake of 39.6%. Furthermore, the AEMs reported in this paper have excellent stability in 1m NaOH solution at 80 °C over 500 h. Therefore, the synthesized polymers offer a new insight into the design of high performance materials for AEMs. Abstract : It is still a challenge to obtain high‐performance anion exchange membranes along with high ion conductivity and the ability to suppress swelling for alkaline fuel cell applications. Here, a series of poly(ether sulfone)s with large planar units attached using flexible alkyl imidazolium pendants is synthesized by a rational strategy.